EFFECT OF CADMIUM CHLORIDE ON THE FREE AMINO ACIDS AND TRANSAMINASES (GOT & GPT) DURING THE ADULT LIFE OF HENOSEPILACHNA VIGINTIOCTOPUNCTATA (FABR.) (INSECTA) - KAUR, SURINDER PAL; SIDHU, DALBINDER SINGH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2005)
The biochemical effect of Cadmium chloride on the free amino acids and transaminases (GOT & GPT) during the adult life of Henosepilachna vigintioctopunctata (Fabr) has been studied in the present research work. The observations reveal that the chemicals under references show a significant decrease in the treated cohorts in comparison to the controlled adults of H. vigintioctopunctata. The reproductive potential of the insect has also been evaluated which indicates clearly that this chemical qualifies as a chemosterilant. The observations project sterility in these insects above 80%.